Dynamic Behavior of Advanced Materials and Structures - Song, Weidong; Xiao, Lijun; Yang, Xianfeng (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
With the growing use of advanced materials and structures in extreme environments—such as under high-speed impacts and explosions—understanding their dynamic response has become crucial. This Special Issue, “Dynamic Behavior of Advanced Materials and Structures”, explores the mechanical performance of metamaterials, composites, and lightweight sandwich structures under dynamic loading. By investigating their behavior in extreme conditions, researchers can optimize materials and enhance structural safety and reliability. Featuring ten publications (nine research articles and one review), this issue highlights cutting-edge theoretical, experimental, and simulation studies. The included Editorial provides a concise overview of these contributions, offering valuable insights for engineers and scientists in the field.